Progress in Physical Chemistry Volume 4 : Ionic Motion in Materials with Disordered Structures - From Elementary Steps to Macroscopic Transport. - Funke, Klaus (De Gruyter, 2011)
This fourth volume of the series ""Progress in Physical Chemistry"" is a collection of mini-review articles written by those who were project leaders and members of the Collaborative Research Centre (SFB) 458 of the German Research Foundation (DFG). The articles are based on ten years of intense coordinated research and report particularly on the scientific progress made at SFB 458 since 2005. Their common theme is the study of ionic motion in disordered materials over wide scales in space and time. The mini reviews thus address key questions in the rapidly developing field of SOLID STATE IONI.